Impact of regular aspirin use on overall and cancer-specific survival in patients with colorectal cancer harboring a PIK3CA mutation. (April 2015) - Kothari, Nishi; Kim, Richard; Jorissen, Robert N.; Desai, Jayesh; Tie, Jeanne; Wong, Hui-Li; Farragher, Ian; Jones, Ian; Day, Fiona L.; Li, Shan; Sakthinandeswaren, Anuratha; Palmieri, Michelle; et al.
Abstract Background. Recent data have suggested that regular aspirin use improves overall and cancer-specific survival in the subset of colorectal cancer (CRC) patients harboring PIK3CA mutations. However, the number of PIK3CA-mutated CRC patients examined in these studies was modest. Our collaborative study aims to validate the association between regular aspirin use and survival in patients with PIK3CA-mutated CRC. Patients and methods. Patients with PIK3CA-mutated CRC were identified at Moffitt Cancer Center (MCC) in the United States and Royal Melbourne Hospital (RMH) in Australia. Prospective clinicopathological data and survival data were available. At MCC, PIK3CA mutations were identified by targeted exome sequencing using the Illumina GAIIx Next Generation Sequencing platform. At RMH, Sanger sequencing was utilized. Multivariate survival analyses were conducted using Cox logistic regression. Results. From a cohort of 1487 CRC patients, 185 patients harbored a PIK3CA mutation. Median age of patients with PIK3CA-mutated tumors was 72 years (range: 34–92) and median follow up was 54 months. Forty-nine (26%) patients used aspirin regularly. Regular aspirin use was not associated with improved overall survival (multivariate HR 0.96, p = 0.86). There was a trend towards improved cancer-specific survival (multivariate HR 0.60, p = 0.14), but this was not significant. Conclusions. Despite examining a large number of patients, we did not confirm that regular aspirin use was associated with statistically significant improvements in survival in PIK3CA-mutated CRC patients. Prospective evaluation of this relationship is warranted.